Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/09637486.2012.690024
|View full text |Cite
|
Sign up to set email alerts
|

Potato consumption and cardiovascular disease risk factors among Iranian population

Abstract: We found a positive relation between potato consumption, high fasting blood glucose level and diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…Among those that have, higher intake of potatoes, including boiled and baked potatoes, is prospectively linked to incidence of diabetes, while potatoes, corn, and peas are linked to greater long-term weight gain, in contrast to nonstarchy vegetables which are associated with protection against weight gain and diabetes. 28, 55, 146, 147 Potatoes have also been cross-sectionally linked to greater diabetes, higher blood glucose, and lower HDL-C; 148 and, in retrospective studies, higher risk of stroke. 149 Based on these concerns, russet/white potatoes are generally excluded from recommendations to increase vegetable consumption.…”
Section: Foods and Cardiometabolic Healthmentioning
confidence: 99%
“…Among those that have, higher intake of potatoes, including boiled and baked potatoes, is prospectively linked to incidence of diabetes, while potatoes, corn, and peas are linked to greater long-term weight gain, in contrast to nonstarchy vegetables which are associated with protection against weight gain and diabetes. 28, 55, 146, 147 Potatoes have also been cross-sectionally linked to greater diabetes, higher blood glucose, and lower HDL-C; 148 and, in retrospective studies, higher risk of stroke. 149 Based on these concerns, russet/white potatoes are generally excluded from recommendations to increase vegetable consumption.…”
Section: Foods and Cardiometabolic Healthmentioning
confidence: 99%
“…They have demonstrated promising effects in a wide variety of diseases such as cancer [16,17] , diabetes [18,19] , atherosclerosis and cardiovascular diseases [20][21][22][23] , learning and cognitive complications [24][25][26] , and wounds [27][28][29] . Furthermore, medicinal herbs are also effective in prevention and treatment of the toxicity induced by other drugs or toxins [30][31][32][33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…It has also shown that medicinal plants, rich in antioxidants, may ameliorate hyperlipidemia,[131415] other than reduction of diabetic or atherosclerosis complications. [16] These plants mostly include phenolic and flavonoid components with antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%